A Study of Henry Mckee Woods’s Missionary Work in China - YANG, Jianlong (Journal of Research for Christianity in China (JRCC), 2025)
In the late 19th and early 20th centuries, Christianity in China underwent significant expansion and localization. Henry McKee Woods (1857–1943), a missionary of the Presbyterian Church in the United States, dedicated over forty years to evangelism and social service in Zhenjiang, Qingjiangpu, and Huai’an, Jiangsu Province. He actively participated in the translation of the Mandarin Union Version of the Bible and published works such as A Commentary on the Four Books, Adapted to Modern Times and A Commentary on the Five Classics, Adapted to Modern Times, exploring the interaction between Christianity and Chinese culture. Woods also promoted medical missions, social relief, and anti-opium campaigns, creating a model of integrated ministry combining medicine, preaching, and education. His vision of “unity in diversity” emphasized spiritual unity amid denominational diversity, inspiring the Global Revival Prayer Movement and setting an enduring model for contextual mission work and cross-denominational cooperation in modern Chinese Christian history.